Platelet‐Rich Plasma Vs Autologous Blood Vs Corticosteroid Injections in the Treatment of Lateral Epicondylitis: A Systematic Review, Pairwise and Network Meta‐Analysis of Randomized Controlled Trials. Issue 4 (13th January 2020) - Tang, Siqi; Wang, Xiaoshuai; Wu, Peihui; Wu, Peiqi; Yang, Jiaming; Du, Zefeng; Liu, Shaoyu; Wei, Fuxin
Abstract : Objective: To compare the effectiveness of platelet‐rich plasma (PRP), autologous blood (AB), and corticosteroid injections in patients with lateral epicondylitis. Type of Study: Network meta‐analysis. Literature Survey: Randomized controlled trials (RCTs) that compared any two forms of injections among PRP, AB, and corticosteroid for the treatment of lateral epicondylitis were searched from inception to 30 November 2018, on PubMed, Embase, and Cochrane library. Methodology: Two researchers independently selected and assessed the quality of RCTs with the Cochrane Risk of Bias Tool. All relevant data from the included studies were extracted and heterogeneity was checked by Cochran's Q test and inconsistency statistic (I 2 ). Publication bias was evaluated by constructing contour‐enhanced funnel plots. Stata 15 software was applied for pairwise meta‐analysis and network meta‐analysis. To explore the efficacy between different follow‐up periods, we considered the duration within 2 months to be short term, whereas 2 months or more was considered long term. Synthesis: Twenty RCTs (n = 1271) were included in this network meta‐analysis. According to ranking probabilities, corticosteroid ranked first for visual analog score (VAS) (surface under the cumulative ranking [SUCRA] = 90.7), modified Nirschl score (82.9), maximum grip strength (69.5), modified Mayo score (MMS) (77.9), and Patient‐Related Tennis Elbow Evaluation (PRTEE) score (93.3) for the short‐term period. For the long‐term period, PRP ranked first for VAS (94.3), pressure pain threshold (99.8), Disabilities of Arm Shoulder and Hand (DASH) score (75.2), MMS (88.2), and the PRTEE score (81.8). Conclusion: PRP was associated with more improvement in pain intensity and function in the long term than were the comparators. However, in the short term, corticosteroids were associated with the most improvement.